The influence of surface treatment on hydrophobicity, protein adsorption and microbial colonisation of silicone hydrogel contact lenses - Santos, Lívia (2007)
Purpose: To evaluate the influence of surface treatment of silicone-hydrogel CL on lens hydrophobicity, protein adsorption and microbial colonisation by studying several silicone hydrogel contact lenses (CL) with and without surface treatment. The lenses used in this study were Balafilcon A, Lotrafilcon A, Lotrafilcon B and Galyfilcon A. A conventional hydrogel CL (Etafilcon A) was also tested. Methods: Hydrophobicity was determined through contact angle measurement using the advancing type technique on air. The type and quantity of proteins adsorbed were assessed through SDS-PAGE and fluorescence spectroscopy, respectively. Microbial colonisation was studied by removing the microbes from the lenses through sonication, and counting the colony-forming units on agar plates. Results: Regarding hydrophobicity, both surface and non-surface-treated silicone hydrogel CL were found to be hydrophobic, and the conventional hydrogel CL was found to be hydrophilic. Concerning protein adsorption, different protein profiles were observed on the several lenses tested. Nevertheless, the presence of proteins with the same molecular weight as lysozyme and lactoferrin was common to all lenses, which is probably related to their abundance in tears. In terms of total protein adsorption, silicone hydrogel CL did not exhibit any differences between themselves. However, the conventional hydrogel Etafilcon A adsorbed a larger amount of proteins. Regarding microbial colonisation, Balafilcon A exhibited the greatest amount of colonising microbes, which can be due to its superior hydrophobicity and higher electron acceptor capacity. Conclusion: This study suggests that silicone hydrogel lenses adsorb a lower amount of proteins than the conventional hydrogel lenses and that this phenomenon is independent of the presence of surface treatment. Concerning microbial colonisation, the surface treated Balafilcon A, exhibited a greater propensity, a fact that may compromise the lens wearer’s ocular health.